PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMAN 14 PEKANBARU - Umi Laeliyah; R. Usman Rery; Maria Erna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purposes of research are to know the improvement of student learning achievement and value of influence by implementing learning model Creative Problem Solving (CPS) on the hydrocarbon subject at the class X SMA N 14 Pekanbaru. CPS learning model includes steps problem clarify, disclosure ideas, evaluation and election ideas also implementation elected idea. This research is experimental research using Design Randomized Control Group Pretest-Posttest. The research sample consisted two class, class X 1 as experiment class and class X 7 as control class that has tested by normality test using Liliefors test and homogeneity test using equality of two average test.. Hypothesis was done by using test-t right side. Research result shown that the implementation of learning model CPS can improve student learning achievement on the hydrocarbon subject where tarithmetic = 7,71 > ttable = 2,00 with value of its influence to student learning achievement is 45,22%.Keywords : Learning Model, Creative Problem Solving (CPS), Learning Achievement, Hydrocarbon